Cholecystokinin from the entorhinal cortex enables neural plasticity in the auditory cortex - Li, Xiao (Nature Publishing Group, 2014)
Patients with damage to the medial temporal lobe show deficits in forming new declarative memories but can still recall older memories, suggesting that the medial temporal lobe is necessary for encoding memories in the neocortex. Here, we found that cortical projection neurons in the perirhinal and entorhinal cortices were mostly immunopositive for cholecystokinin (CCK). Local infusion of CCK in the auditory cortex of anesthetized rats induced plastic changes that enabled cortical neurons to potentiate their responses or to start responding to an auditory stimulus that was paired with a tone that robustly triggered action potentials. CCK infusion also enabled auditory neurons to start responding to a light stimulus that was paired with a noise burst. In vivo intracellular recordings in the auditory cortex showed that synaptic strength was potentiated after two pairings of presynaptic and postsynaptic activity in the presence of CCK. Infusion of a CCK(B) antagonist in the auditory cortex prevented the formation of a visuo-auditory association in awake rats. Finally, activation of the entorhinal cortex potentiated neuronal responses in the auditory cortex, which was suppressed by infusion of a CCK(B) antagonist. Together, these findings suggest that the medial temporal lobe influences neocortical plasticity via CCK-positive cortical projection neurons in the entorhinal cortex.